The Experience of Parenting a Child With Disability in Old Age. Issue 4 (July 2017) - Band‐Winterstein, Tova; Avieli, Hila
Abstract: Background: There are growing numbers of older parents providing ongoing care for adults with disabilities. A parent's aging calls for a redefinition of parental care practices and roles in light of his or her own changing needs. Purpose: The current study aims to highlight the ways in which aging parents perceive and construct their parental role to adult children with disabilities at this point in their lives. Methods: An interpretive phenomenological analysis perspective was used. Data collection was performed through in‐depth, semistructured interviews with 20 aging parents of children with developmental disabilities, followed by a content analysis. Results: Four patterns of parental identity emerged: "Being happy is his responsibility; I did my part, " embracing aging needs; "I can do part‐time worrying, " a gradual letting go of parental roles; "I'm worn out, but I keep going. What choice do I have?" bearing the brunt; "I'm an old woman changing diapers, " full‐time parents. Conclusions: The findings enable a deeper understanding of the various ways in which parents cope with aging alongside caring for an adult child with disability. Hence, this study can serve as a framework for developing tailored and differential intervention methods for these families. Clinical Relevance: As the world's people experience longer life expectancy, of both individuals with disabilities and their parents, nurses' education and practice should be challenged by the double sensitivities of elder's caregiving and address the unique needs of this unique population.